Evaluasi Penerapan SAK ETAP pada Koperasi Karyawan “Respati’ Universitas Respati Yogyakarta - Adiputra, Andre Kussuma; Muntari, Sri; Eko Christmawan, Poly Endrayanto (RJABM (Research Journal of Accounting and Business Management), 2023)
This research was conducted to find out how measurement, recognition, presentation, and disclosure of report elements in financial reporting of cooperatives based on financial accounting standards of entities without public accountability in the "Respati" cooperative at Respati University, Yogyakarta.The method used in this study is descriptive qualitative using primary data in the form of interviews with the management of the Respati Employee Cooperative and secondary data in the form of the Respati Employee Cooperative Financial Statements. The results of this research are that the Respati Employee Cooperative has prepared financial reports but they are not complete and have not implemented SAK ETAP in preparing their overall financial statements.Based on the results of this study, it is suggested that the Respati Employee Cooperative start paying attention to its Financial Statements so that they are more in line with SAK ETAP in force in 2018, make complete and detailed records, calculate depreciation of fixed assets owned, and present complete Financial Statements.